Motor Recovery of the Affected Hand in Subacute Stroke Correlates with Changes of Contralesional Cortical Hand Motor Representation - Jitka Veldema; Kathrin Bösl; Dennis Alexander Nowak (Neural Plasticity)
Objective. To investigate the relationship between changes of cortical hand motor representation and motor recovery of the affected hand in subacute stroke. Methods. 17 patients with motor impairment of the affected hand were enrolled in an in-patient neurological rehabilitation program. Hand motor function tests (Wolf Motor Function Test, Action Research Arm Test) and neurophysiological evaluations (resting motor threshold, motor evoked potentials, motor map area size, motor map area volume, and motor map area location) were obtained from both hands and hemispheres at baseline and two, four, and six weeks of in-patient rehabilitation. Results. There was a wide spectrum of hand motor impairment at baseline and hand motor recovery over time. Hand motor function and recovery correlated significantly with (i) reduction of cortical excitability, (ii) reduction in size and volume of cortical hand motor representation, and (iii) a medial and anterior shift of the center of gravity of cortical hand motor representation within the contralesional hemisphere. Conclusion. Recovery of motor function of the affected hand after stroke is accompanied by definite changes in excitability, size, volume, and location of hand motor representation over the contralesional primary motor cortex. These measures may serve as surrogate markers for the outcome of hand motor rehabilitation after stroke.